Innovation in Mission-Based Statistics Learning through Student Cooperative Partnership at MTsN 4 Mojokerto - Pamiluwati (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study aims to describe the implementation and outcomes of mission-based statistics learning innovation through student cooperative partnerships as a contextual learning medium in the eighth grade at MTs Negeri 4 Mojokerto during the 2024–2025 academic year. This innovation is designed to enhance students' understanding of statistical concepts and data literacy by utilizing authentic data from the student cooperative. The mission-based learning model, which includes the phases of Observation, Investigation, Simulation, and Interpretation, is applied to create a more active, meaningful, and student-centered learning experience. The findings of this study show that student cooperative-based learning is effective in improving students' learning outcomes in cognitive, skill, and attitude aspects. A significant improvement was observed in post-test scores compared to pre-test scores. Students became more proficient in constructing tables and graphs, and there was an increase in group collaboration and engagement during the learning process. Additionally, this approach also enhanced students' mathematical communication skills, boosted their confidence in presenting data, and sparked an interest in economic activities and entrepreneurship. Overall, this innovation proves effective in creating contextual and relevant learning experiences, while supporting the strengthening of students' numerical literacy. This approach can be applied as an alternative model for learning that involves real data in the school environment.